2020
DOI: 10.20944/preprints202011.0339.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction between Fibroblasts and Immune Cells Following DNA Damage Induced by Ionizing Radiation

Abstract: Cancer-associated fibroblasts (CAF) form the basis of tumor microenvironment and possess immunomodulatory functions by interacting with other cells surrounding tumor, including T lymphocytes, macrophages, dendritic cells and natural killer cells. Ionizing radiation is a broadly-used method in radiotherapy to target tumors. In mammalian cells, ionizing radiation induces various types of DNA damages and DNA damage response. Being unspecific, radiotherapy affects all the cells in tumor microenvironment, including… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It was previously shown that the expression and activity of DNA-PKcs are increased in the NSPC murine cells when compared to mouse embryonic fibroblasts [ 26 ], suggesting that DNA-PKcs can be essential for homeostasis of NSPCs. Expression and activity of NHEJ vary in different cell types and require closer attention in future research [ 33 ]. Our data further highlighted this observation, and our findings suggest that the DNA-PKcs is required for NSPC proliferation and self-renewal capacities, although its role is partially compensated by XLF ( Figure 2 B,C).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the expression and activity of DNA-PKcs are increased in the NSPC murine cells when compared to mouse embryonic fibroblasts [ 26 ], suggesting that DNA-PKcs can be essential for homeostasis of NSPCs. Expression and activity of NHEJ vary in different cell types and require closer attention in future research [ 33 ]. Our data further highlighted this observation, and our findings suggest that the DNA-PKcs is required for NSPC proliferation and self-renewal capacities, although its role is partially compensated by XLF ( Figure 2 B,C).…”
Section: Discussionmentioning
confidence: 99%
“…An important consequence that may take shape because of RT is chronic inflammation that drives fibrosis and leads to an increase in stromal members in the TME as well as more ECM components ( Straub et al, 2015 ). CAFs tolerate relatively high doses (30 Gy) of radiation without apoptosis; however, doses higher than 10–12 Gy often result in a senescent CAF phenotype ( Ragunathan et al, 2020 ). Premature senescence seems to be also induced in normal human fibroblasts as a result of chronic low dose rate (LDR) exposure (5 or 15 mGy/h) of gamma rays ( Fujimori et al, 2005 ).…”
Section: The Effects Of Cancer Therapies On Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Cells will immediately initiate apoptosis, once DNA damage repair fails (15,16). 0.5-1Gy irradiation can induce DNA damage and apoptosis for peripheral blood lymphocytes which are very sensitive to irradiation (17,18). P53 signaling pathway plays an extremely important role in both DNA damage repair and the initiation of apoptosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, P53 is activated and the stability of P53 is enhanced, which result in cell cycle arrest at G1/S phase and provide a critical opportunity for cells to restore genomic integrity prior to DNA replication. Repairable DNA damage tends to be transient, whereas sustained P53 activation will induce the cells to initiate apoptotic program (17,22). P53 signal plays an important regulatory role in the whole process of ionizing radiation-induced DNA damage and lymphocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%